The expansion of Choppies into Africa - Beder, Laurence; Urban, Angela, active 2016 (London : Wits Business School, 2016)
On a Saturday morning in early October 2015, Choppies chief executive officer (CEO), Ramachandran Ottapathu, made his weekly visit to a Choppies store. While watching the familiar scenes in the Choppies superstore in Gaborone, he considered the company's strategy to extend its African footprint.Choppies was the leading supermarket chain in Botswana, targeting the lower- to middle-income sectors. The company had 134 stores in three countries: 75 in Botswana, 38 in South Africa and 21 in Zimbabwe. Its major strategic objective was to increase its overall number of stores to 200, and the number of African countries it operated in to six, by the end of 2016. Ottapathu wondered how Choppies could achieve this objective while still growing value for shareholders.
Originally published in Beder, L., & Urban, A. (2016). The expansion of Choppies into Africa. WBS-2016-5. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; Ottopathu, Ramachandran; Choppies; Small business -- Growth; Botswana; South Africa; Zimbabwe; Gaborone (Botswana); electronic books; Gaborone (Botswana)